Implementasi Metode Extreme Programming dalam Sistem Informasi Manajemen Pemesanan Barang Online - Icha Riani; Rayyan Firdaus (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
The online goods ordering information system is an application that allows customers to order goods practically via the internet. The Extreme Programming (XP) software development method is an approach that can be used to develop information systems with a focus on flexibility and responsiveness to changing user needs. This research aims to implement the Extreme Programming method in developing an online goods ordering information system. The research method used is a literature study to identify the basic concepts of Extreme Programming and analysis of the design of an online goods ordering information system. The research results show that the implementation of the Extreme Programming method in developing an online goods ordering information system can increase flexibility in dealing with changing user needs and improve the quality of the software produced.